Analysis of Causality and Forcasting between Electricity Consumption and Economic Growth in Indonesia - Sari, Sari (Valid: Jurnal Ilmiah, 2025)
The main objective of this study is to examine relationship between electricity consumption from 4 sectors which are household, commercial, industrial, transportation toward economic growth using data from 2001 to 2023 by applying the autoregressive distributed lag (ARDL) model. Other variables such as capital and labor that affect economic growth are also added. Data obtained from the Central Bureau of Statistics, World Bank. To see the relationship between variables, a Granger causality test is carried out. Modeling using the ARDL method is used to see long-term and short-term relationships. Furthermore, forecasting is also carried out to see the achievement of economic growth targets. The findings that commercial electricity consumption, industrial electricity consumption, transportation electricity consumption have a one-way causal relationship with economic growth or the growth hypothesis accepted. While household electricity consumption does not have a causal relationship with economic growth. Based on the ARDL method, there is a long-term relationship. Electricity consumption scenario of each sector can achieve the economic growth target with the household sector 20.4%, commercial 8.9%, industry 40% and transportation 28.3%. and constant capital growth of 2% per year, average increase in the number of workers of 2% per year.